Impact of publicly available vaccination rates on parental school and child care choice. Issue 30 (16th July 2018) - Cataldi, Jessica R.; Dempsey, Amanda F.; Allison, Mandy A.; O'Leary, Sean T.
Highlights: Preferences for school/child care choice and predicted behaviors were measured. In this context, parents value knowing school/child care vaccination rates. Vaccine-hesitant and non-hesitant parents value vaccination rate information. Reporting these rates may affect school/child care choice. Abstract: Objective: Several states require schools and child cares to report vaccination rates, yet little is known about the impact of these policies. Our objectives were to assess: (1) predicted impact of vaccination rates on school/child care choice, (2) differences between vaccine hesitant and non-hesitant parents, and (3) differences by child's age. Methods: In 2016, a cross-sectional email survey of Colorado mothers with children ≤12 years old assessed value of vaccination rates in the context of school/child care choice. A willingness-to-pay framework measured preference for schools/child cares with different vaccination rates using tradeoff with commute time. Results: Response rate was 42% (679/1630). Twelve percent of respondents were vaccine hesitant. On a scale where 1 is "not important at all" and 4 is "very important" parents rated the importance of vaccination rates at 3.08. Respondents (including vaccine-hesitant respondents) would accept longer commutes to avoid schools/child cares with lower vaccination rates. Parents of child-care-age children were more likely to consider vaccination rates important. Conclusions: This study shows parents highly value vaccination rates in the context of school and child care choice. Both hesitant and non-hesitant parents are willing to accept longer commute times to protect their children from vaccine-preventable diseases.